PENGARUH PARTISIPASI PEMAKAI AKUNTANSI, KEMAMPUAN TEKNIK PERSONAL DAN PERAN PENGAWAS INTERNAL TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA ORGANISASI PERANGKAT DAERAH (OPD) KABUPATEN INDRAGIRI HILIR - SURYANI SURYANI (Fakultas Ekonomi Universitas Islam Indragiri, 2022)
This study aims to examine and obtain empirical evidence of the influence of the participation of users of accounting information systems, personal technical abilities, and the role of internal supervisors on the effectiveness of the accounting informant system in the Regional Apparatus Organization (OPD) of Indragiri Hilir Regency. The population in this study were employees of the finance department at the OPD of Indragiri Hilir Regency. The sample selection was done by purposive sampling, so the number of samples was 102 respondents who matched the criteria. Data analysis methods include validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test and multiple regression analysis, coefficient of determination test and hypothesis testing using SPSS version 26 software to process the data. The data collected were analyzed by descriptive techniques and multiple regression statistics. Based on the results of the analysis, it was known that the variables of accounting information system user participation, personal engineering ability, and the role of internal supervisors affect the effectiveness of accounting information systems